The rationale behind interfirm tender offers - Bradley, Michael; Desai, Anand; Kim, E.Han (Journal of Financial Economics, 1983)
This paper investigates the rationale behind interfirm tender offers by examining the returns realized by the stockholders of firms that were the targets of unsuccessful tender offers and firms that have made unsuccessful offers. Our results suggest that the permanent positive revaluation of the unsuccessful target shares [documented by Dodd and Ruback (1977) and Bradley (1980)] is due primarily to the emergence of and/or the anticipation of another bid that would ultimately result in the transfer of control of the target resources. We also find that the rejection of a tender offer has differential effects on the share prices of the unsuccessful bidding firms depending upon whether the tender offer process results in a change in the control of target resources. On the basis of these results we conclude that acquisitions via tender offers are attempts by bidding firms to exploit potential synergies, not simply superior information regarding the ‘true’ value of the target resources.